2022
DOI: 10.1039/d2re00310d
|View full text |Cite
|
Sign up to set email alerts
|

Development of a modular photoreactor for the upscaling of continuous flow photochemistry

Abstract: The upscaling of biphasic photochemical reactions is challenging because of the inherent constraints of liquid-gas mixing and light penetration. Using semi-permeable coaxial flow chemistry within a modular photoreactor, the photooxidation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…5-Acyloxy butenolides are readily synthesized in one step from the parent hydroxy butenolide HB , itself obtainable at a 100 gram-scale via continuous photooxygenation of furfural using our recently introduced photoflow reactor . Acylation of this cyclic hemiacetal with anhydrides or acyl chlorides , afforded esters 2 and carbonates 3 , whereas we found that the tin-catalyzed reaction with isocyanates produces carbamates 4 in high yields (Figure ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…5-Acyloxy butenolides are readily synthesized in one step from the parent hydroxy butenolide HB , itself obtainable at a 100 gram-scale via continuous photooxygenation of furfural using our recently introduced photoflow reactor . Acylation of this cyclic hemiacetal with anhydrides or acyl chlorides , afforded esters 2 and carbonates 3 , whereas we found that the tin-catalyzed reaction with isocyanates produces carbamates 4 in high yields (Figure ).…”
Section: Resultsmentioning
confidence: 88%
“…We have recently introduced 5-alkoxy butenolides 1 as a very versatile bio-based alternative for acrylates in coating compositions (Figure ). − , These acetals are readily prepared from the condensation of alcohols onto hydroxy butenolide HB , itself obtained via highly selective and quantitative photooxygenation of the platform chemical furfural (Figure B) . In our prior work, it was shown that substitution with an electron-withdrawing alkoxy substituent at the 5-position allows for smooth copolymerization of this butenolide subclass with vinyl ethers and esters, affording polymers and coatings with a high content of bio-based carbon in excellent yields.…”
Section: Introductionmentioning
confidence: 99%
“…Having demonstrated that juglone can act as an efficient photocatalyst in different solvents, with applications to a variety of substrates without noticeable new side product formation compared to conventional photocatalysts, we investigated the transposition of the β-citronellol in CH 3 CN photooxidation in a continuous flow photoreactor. Given the enhancement in mass transfer and surface area, such strategies have found widespread use in photooxidation chemistry. , …”
Section: Resultsmentioning
confidence: 99%
“…Visible light photochemistry is particularly appealing from a green chemistry standpoint, as it enables a large variety of chemical transformations to operate under very mild conditions. Because most organic compounds do not absorb visible light, the main method of driving such processes is to use a photocatalyst (also called a “photosensitizer”) to transfer electrons or energy to a given substrate upon excitation by one or multiple photons. These processes can be mediated by either organic or organometallic photocatalysts, such as rose bengal, porphyrins, methylene blue (MB), or ruthenium trisbipyridine salts, to name a few. Such photocatalysts and their derivatives have been widely used in organic synthesis, particularly in the context of singlet oxygen ( 1 O 2 ) mediated photooxidations (in this context the term “photosensitizer” is more appropriate) .…”
Section: Introductionmentioning
confidence: 99%
“…1A). 75,76 Indeed, the development of sustainable materials such as catalysts, 20,[77][78][79] polymers, 80,81 coatings 82,83 and molecular motors 84 from renewable and earth abundant sources has received high priority in the past, avoiding dependency on fossil resources. Considering element scarcity and climate change, iron is the fourth most abundant element in the earth's crust and the most abundant metal, and thus an ideal candidate as an environmental photocatalyst material.…”
Section: Introductionmentioning
confidence: 99%